HIV Prevalence among Pregnant Women in Brazil: A National Survey - Gerson Fernando Mendes Pereira; Meritxell Sabidó; Alessandro Caruso; Silvano Barbosa de Oliveira; Fábio Mesquita; Adele Schwartz Benzaken (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Background This study was conducted to determine the seroprevalence of HIV among pregnant women in Brazil and to describe HIV testing coverage and the uptake of antenatal care (ANC). Methods Between October 2010 and January 2012, a probability sample survey of parturient women aged 15-49 years who visited public hospital delivery services in Brazil was conducted. Data were collected from prenatal reports and hospital records. Dried blood spot (DNS) samples were collected and tested for HIV.We describe the agespecific prevalence of HIV infection and ANC uptake with respect to sociodemographic factors. Results Of the 36,713 included women, 35,444 (96.6%) were tested for HIV during delivery admission. The overall HIV prevalence was of 0.38% (95% confidence interval [CI]: 0.31-0.48), and it was highest in: the 30 to 39 year-old age group (0.60% [0.40- 0.88]), in the Southern region of Brazil (0.79% [0.59-1.04]), among women who had not completed primary (0.63% [0.30-1.31]) or secondary (0.67% [0.49-0.97]) school education, and among women who self-reported as Asian (0.94% [0.28-3.10]). The HIV testing coverage during prenatal care was of 86.6% for one test and of 38.2% for two tests. Overall, 98.5% of women attended at least 1 ANC visit, 90.4% attended at least 4 visits, 71% attended at least 6 visits, and 51.7% received ANC during the 1st trimester. HIV testing coverage and ANC uptake indicators increased with increasing age and education level of education, and were highest in the Southern region. Conclusions Brazil presents an HIV prevalence of less than 1% and almost universal coverage of ANC. However, gaps in HIV testing and ANC during the first trimester challenge the prevention of the vertical transmission of HIV. More efforts are needed to address regional and social disparities.